The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4314/tjpr.v14i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Compounds of M(II) Biometal Ions with Acid- Type Anti-inflammatory Drugs as Ligands – A Review

Abstract: The cations of biometals in biological systems easily interact with various moieties of organic and inorganic biomolecules, either as natural constituents or after introduction into the body via O-, N-and S-donor atoms. Study of the interaction between M(II) biometal-O-donor ligand (drug) is of interest for various reasons: more evenly dosing of medicine and biodistribution of medicine; monitoring of its pharmacokinetics including excretion; reduction of unwanted effects of the medicine; greater antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 57 publications
0
45
0
1
Order By: Relevance
“…The study of the interaction of bio-metal ion M(II) and O-donor ligand (used as a drug) is interesting for several important reasons: in order to achieve a uniform drug dosage and bio-distribution, monitoring its pharmacokinetic and excretion, better antimicrobial, antitumor and antiulcer activity, and reduction of undesirable effects of the drug. 1,2,3 According to the literature data, products of the interaction of M(II) ions with N-donor ligands were studied by the spectroscopic methods in order to obtain a pharmaceutical product with better pharmacological and antitumor effects. 4,5 In this paper, the interactions of Fe(II) and Mn(II) ions with an antitumor drug named capecitabine (CPC) were studied by FT-IR and UV/Vis spectroscopy and obtained products were closely defined.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the interaction of bio-metal ion M(II) and O-donor ligand (used as a drug) is interesting for several important reasons: in order to achieve a uniform drug dosage and bio-distribution, monitoring its pharmacokinetic and excretion, better antimicrobial, antitumor and antiulcer activity, and reduction of undesirable effects of the drug. 1,2,3 According to the literature data, products of the interaction of M(II) ions with N-donor ligands were studied by the spectroscopic methods in order to obtain a pharmaceutical product with better pharmacological and antitumor effects. 4,5 In this paper, the interactions of Fe(II) and Mn(II) ions with an antitumor drug named capecitabine (CPC) were studied by FT-IR and UV/Vis spectroscopy and obtained products were closely defined.…”
Section: Introductionmentioning
confidence: 99%
“…[11] The structural characteristics, medicinal/veterinary properties, superoxide dismutase (SOD) activity [SOD is an enzyme that catalyzes the dismutation of the superoxide (O 2 -) radical into both ordinary molecular oxygen (O 2 ) and hydrogen peroxide (H 2 O 2 ), thus being involved in the inflammation mechanism], anti-inflammatory, and ulcerogenic effects of Cu-NSAIDs have also been reviewed. Coordinated metal ions with NSAIDs provide advantages over the drugs themselves.…”
mentioning
confidence: 99%
“…Thus, if a given NSAIDs-metal complex remains intact in the biological medium its biological target is [a] She is now a Postdoctoral Fellow of the National Scholarships Foundation of Greece-Siemens program with a fellowship of excellence. [11,14] Scheme 12.The anti-inflammatory effects of 9 {[Cu(asp) 2 ] 2 , Scheme 12} were also tested. Sotiris K. Hadjikakou was born in Famagusta, Cyprus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Encouragingly, some metal-NSAID complexes exhibit greater cytotoxicity than cisplatin. A recent comprehensive review It should be noted that several metal-NSAIDs have been previously reported, and their binding to biomolecules such as DNA and human serum albumin (HSA) has been well characterized using spectroscopic methods [48][49][50][51][52]. In general, metal-NSAID complexes display stronger binding to biomolecules than the corresponding free NSAID.…”
Section: Introductionmentioning
confidence: 99%